Mediating role of exercise in the relationship between body dissatisfaction and overeating using structural equation modeling - Zhimin Yi; Wenjing Yan; Guohuan Hua; Ying Wang; Chunmei Wu; Guoqiu Liu; Ming Hao (BMC Public Health)
Abstract Background With the rapid development of society, teenagers have more access to individuals with perfect bodies and are becoming more concerned about their body image. Currently, few studies assess body image and eating disorders comprehensively in China. Given the seriousness of these issues, there is an urgent need to understand the current state of body image and eating behaviors among Chinese people and formulate preventive strategies. Methods In this study, 1711 college students between 17 and 23 years old in southern China completed relevant anthropometric measurements, essential information and three questionnaires. Multiple linear regression was used to screen the variables, and sex invariant analysis was used to determine whether to separate men and women to fit the structural equation model. Finally, the path diagram of the structural equation model was used to explore the complex relationship between body dissatisfaction and overeating. Results Our results found that 69.4% of participants with a body mass index (BMI) within the normal range were dissatisfied with their weight. Further, body dissatisfaction directly or indirectly leads to overeating. Additionally, exercise played a mediating role in the body dissatisfaction and overeating of college students. Conclusions If BMI directs body dissatisfaction, it may lead to overeating. As a mediating factor in structural equation modelling, exercise may provide strategies to reduce body dissatisfaction and prevent overeating.